Analysis of Liver Resection Versus Liver Transplantation on Outcome of Small Intrahepatic Cholangiocarcinoma and Combined Hepatocellular‐Cholangiocarcinoma in the Setting of Cirrhosis. Issue 6 (29th May 2020) - De Martin, Eleonora; Rayar, Michael; Golse, Nicolas; Dupeux, Margot; Gelli, Maximiliano; Gnemmi, Viviane; Allard, Marc Antoine; Cherqui, Daniel; Sa Cunha, Antonio; Adam, Rene; Coilly, Audrey; Antonini, Teresa Maria; et al.
Abstract : This multicenter study compares the outcomes of patients with cirrhosis undergoing liver transplantation (LT) or liver resection (LR) between January 2002 and July 2015 who had intrahepatic cholangiocarcinoma (iCCA) or combined hepatocellular‐cholangiocarcinoma (cHCC‐CCA) found incidentally in the native liver. A total of 49 (65%) LT and 26 (35%) LR patients with cirrhosis and histologically confirmed iCCA/cHCC‐CCA ≤5 cm were retrospectively analyzed. LT patients had significantly lower tumor recurrence (18% versus 46%; P = 0.01), for which the median diameter of the largest nodule (hazard ratio [HR], 1.07; 95% confidence interval [CI], 1.02‐1.12]; P = 0.006) and tumor differentiation (HR, 3.74; 95% CI 1.71‐8.17; P = 0.001) were independently predictive. The LT group had significantly higher 5‐year recurrence‐free survival (RFS; 75% versus 36%; P = 0.004). In patients with tumors >2 cm but ≤5 cm, LT patients had a lower recurrence rate (21% versus 48%; P = 0.06) and a higher 5‐year RFS (74% versus 40%; P = 0.06). Independent risk factors for recurrence were LT (protective; HR, 0.23; 95% CI, 0.07‐0.82; P = 0.02), the median diameter of the largest nodule (HR, 1.10; 95% CI, 1.02‐1.73; P = 0.007), and tumor differentiation (HR, 4.16; 95% CI, 1.37‐12.66; P = 0.01). In the LT group, 5‐year survival reached 69% and 65% ( P = 0.40) in patients with tumors ≤2 cm and >2‐5 cm, respectively, and survival was also comparable between iCCA and cHCC‐CCA patients ( P = 0.29). LT may offer a benefit for highly selected patients with cirrhosis and unresectable iCCA/cHCC‐CCA having tumors ≤5 cm. Efforts should be made to evaluate tumor differentiation, and these results need to be confirmed prospectively in a larger population.